Mechanical Instability After Civilian Thoracolumbar Gunshot Injuries: A Systematic Review to Support Classification Development - Guillermo Alejandro Ricciardi; Ignacio Cirillo; Juan Pablo Cabrera; Otávio Vitório Alvarenga Pereira; Emiliano Neves Vialle; Charles Carazzo; Michael Dittmar; Alfredo Guiroy; YURAC BARRIENTOS, RATKO JOVAN; Gregory D. Schroeder (SAGE Publications, 2025)
Study Design Systematic Review.Objectives Identify risk factors for mechanical instability in thoracolumbar gunshot wounds to develop a new classification system.Methods A systematic review following PRISMA 2020 guidelines was conducted across multiple databases from January 1, 1990, to September 12, 2024 (PROSPERO: CRD42023458804).Results Of 2400 records, 33 studies (3195 patients) met inclusion criteria, mostly retrospective and single-center, with varying definitions of instability. Direct comparison was limited due to clinical heterogeneity. Only 12 studies defined mechanical instability, mainly using the Denis three-column theory. Instability was reported in less than 10% of cases, except for one higher-rate outlier. The main markers included vertebral body comminution and potential ligamentous injury. Management was mainly conservative, with a low fixation rate (1.5-9.7%). Imaging relied on CT and static X-rays, with some studies advocating for dynamic radiographs.Conclusion There is a lack of standardized definitions for mechanical instability in civilian thoracolumbar gunshot injuries. Four recurrent unstable patterns were detected, with vertebral body comminution as the most consistent marker. The need for a standardized classification system and further prospective studies is evident.